Metodologia para espacialização do balanço hídrico : aplicação no zoneamento edafoclimático para a seringueira no Espírito Santo - Silva, Kennedy Ribeiro da (2010)
The objective of this work was to develop a method to result on estimative and climate aptitude reports of the elements within the hydro balance for the preparation of an edaphoclimatic zoning for rubber tree’s forestry in Espírito Santo State. It were analyzed the data from 110 pluviometric (weather) stations, considering the data collected between 1977 and 2006. The monthly temperatures were space contextualized using the equations developed by Castro (2008) and data from digital elevation model GTOPO30. The space contextualization of the monthly precipitation had happened starting from the prior selection of spatial interpolators of greater predictive capacity through cross-validation. Thorough the temperature data and monthly precipitation, it was performed the hydro balance in a timely manner for all 110 weather stations. The hydro balance variables were space contextualized by the selection of spatial interpolators of greater predictive capacity through crossvalidation. It was developed a methodology for spatial contextualization of the hydro balance variables, taking as input the entry parameters maps of monthly temperature, monthly precipitation and soils with CADs ranging from 90, 210 to 300 mm. The performance of spatial interpolators and the methodology of spatial variables of the hydro balance was verified with 14 observed stations, allowing a comparison of spatial contextualization methods. Based on thematic maps of average annual temperature, temperature of the coldest month, hydro deficit (obtained through the best spatial contextualization method) and soils map, it was made a reclassification accordingly to the specie’s climatic requirements and, then, beyond the information overlay, obtained that way an edaphoclimatic map for the rubber tree forestry. The results showed that Krigagem interpolator was the most efficient for the spatial contextualization of the monthly precipitation. The spatial contextualization methodology proposal had shown better statistical indexes for the hydro balance variables when compared with traditional methods of interpolation, being this methodology used to generate the hydro deficiency map on the zoning. The most geographical area of the State presents thermal restrictions for rubber tree forestry, with favorable conditions for spread of the Microcylus Ulei fungus.